Characteristics of Betacyanin Natural Food Coloring from Red Dragon Fruit Peel (Water Bath Assisted Solvent Extraction Method): Karakteristik Pewarna Pangan Alami Betasianin dari Kulit Buah Naga Merah (Ekstraksi Metode Water Bath Assisted Solvent Extraction) - Syarifa Ramadhani Nurbaya; Ida Agustini Saidi; Syamsudduha Syahrorini; Miftahul Nahdiya (Academia Open, 2023)
Natural food color are now widely used in food products because they have no side effects that are harmful to the health of the human body. Red dragon skin is one of the sources of natural food coloring. Red dragon skin contains betasianin pigment which produces red-violet. Research aims to determine the effect of the type of solvent and extraction temperature on the characteristics of the Betasianin pigment extract. Betasianin pigment is extracted using the decox method. The parameters measured are colors (L, a, b), pH, and betasianin pigment content. Research uses a randomized group design. Betacyanin pigment from red dragon fruit skin can be extracted using the water bath assisted solvent extraction method. An effective solvent used for the extraction of betacyanin pigment is distilled water and NaCl. Betacyanin pigment can be a natural colorant in food products. Highlights: Optimal Solvent Selection: Distilled water and NaCl are effective solvents for betacyanin pigment extraction, enhancing natural food colorant potential. Influence of Extraction Temperature: Study investigates how extraction temperature impacts betacyanin pigment content and color characteristics. Application in Food Industry: Betacyanin pigment from red dragon fruit skin offers a safe and vibrant natural coloring option for food products. Keywords : betacyanin, extraction, red dragon fruit peel